What is Chronic Constipation? Definition and Diagnosis - James R Gray (Canadian Journal of Gastroenterology)
Although chronic constipation is a common complaint, there are no ideal biological markers for its diagnosis. Diagnosis rests on individual patient perception or clinical criteria developed by expert consensus. Investigation options are multiple but often not necessary. When selected, investigations are directed at confirming the absence of a primary underlying disease, differentiating or defining an alteration in colonic motility or identifying an anorectal evacuation disorder.